The New Economy - E-Business - Kesari, Rajesh; Mishra, Vivek Kumar (Journal of Commerce and Trade, 2012)
Digital business is causing an upheaval that is shaking the foundations of traditional business. More and more companies recognize the opportunity the internet offers and start to establish an online presence with a sound business model behind it. Increased revenues and additional customers who return voluntarily to the company are drivers that bring more and more companies to digitize their offerings. Through the Internet it is possible to invent new and innovative ways to add value to existing products and services without necessarily spending a lot of money. Electronic business is a super set of business cases, which have been digitized and work now on the Internet. An e-business category is defined by the business case and not by the technology used to implement it. Over time more and more type of business will be converted to a digital form, even though it may seem impossible today. Technology is moving fast to make things possible tomorrow, which seemed impossible today.